Micro- and nanotechnology in vaccine development - Skwarczynski, Mariusz; Toth, Istvan (Micro & nano technologies., 2017)
This book provides a comprehensive overview of how use of micro- and nanotechnology (MNT) has allowed major new advance in vaccine development research, and the challenges that immunologists face in making further progress.